Assessment And Intervention of New Learner Anxiety in Junior High School: A Group Case Study - Utari, Ayu Rezki (Syntax Corporation Indonesia, 2024)
This study aims to evaluate the anxiety levels of new students at Junior High School (SMP) and to identify effective interventions to reduce it. A case study was conducted on a group of seventh-grade students at an SMP in Jakarta. The research method used was a quantitative survey with a validated anxiety questionnaire, as well as in-depth interviews to gain a more comprehensive understanding of the factors influencing anxiety. The results showed that high anxiety levels correlate with factors such as adaptation to a new environment, academic pressure, and social relationships. Several interventions implemented included school orientation programs, counseling sessions, and extracurricular activities designed to enhance social skills and self-confidence. These findings are expected to provide guidance for educators and school officials in designing strategies to help new students better adapt to their new school environment.